Conceptual design and structure analysis of giromill vertical axis wind turbine under low wind speed - Hussin, Mohamed Saiful Firdaus; Mukhtar, Mohd Faridduddin; Mohd Tumari, Mohd Zaidi; Mohd Ali, Nursabillilah; Muhamad Damanhuri, Amir Abdullah; Hamdan, Noor Saffreena; Azlan, Khairul Azri; Tofrowaih, Khairul Amri (Penerbit Akademia Baru, 2020)
Unstable wind speed in Malaysia has been a problem for the wind turbine. Vertical axis wind turbine (VAWT) that is placed on the ground causes unnecessary stress and hinderit to perform at maximum performance. Thus, the purpose ofthis study was to analyze the behavior of VAWT at different wind speed. The conceptual design was generated by using the pugh method. Then the structure of the blade was analyzed interms of displacement and von Mises stress, followed by topology optimization. Results showthat peak stress for both forcesapplied and pressure applied was located at the center where maximum displacement is about 5.43x10-6m while the maximum value of von Mises stress is about 0.9763Mpa at the edge of the blade and 0.6641MPa when pressure is distributed uniformly. Based on topology optimization, the blade area can still be reduced at the top and bottom part.